Brazilian Maturity Model for Smart Cities: analysis of the Municipalities of the State of Santa Catarina (Revista Brasileira de Contabilidade e Gestão, 2023)
Never before have so many people lived in urbana reas and this fact requires that cities are prepared to meet the demands of services and infrastructure. In this sense, the objective of this articleis to analyze the performance of six cities in the state of Santa Catarina with better indices of sustain able development through the Brazilian Smart Cities Maturity Model, with data obtained through the Sustainable Municipal Development Indicators System (SIDMS), sponsored by the Santa Catarina Federation of Municipalities (FECAM). Averages were calculated indexes of municipalities to areas of education, health and water, in addition to identifying indicators that influenced the results.
Keywords: sustainability; maturity model; smart cities; SIDMS